2011
DOI: 10.1177/1403494811420325
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to secondhand smoke in Finnish workplaces and compliance with national smoke-free workplace legislation

Abstract: Totally smoke-free workplaces give better protection against the exposure to SHS than workplaces with designated smoking areas. We urge a law reform that does not allow any designated smoking rooms indoors. In the prevention of SHS exposure, special attention should be directed to small workplaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…As could be expected in line with the results of earlier studies [1119], clear socioeconomic differences in adolescents’ ETS exposure were found in favour of those with higher socioeconomic backgrounds. Despite studies have found this association, little is known about the potential pathway accounting for these relationships; and it still remains largely without explanation by this study, too.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As could be expected in line with the results of earlier studies [1119], clear socioeconomic differences in adolescents’ ETS exposure were found in favour of those with higher socioeconomic backgrounds. Despite studies have found this association, little is known about the potential pathway accounting for these relationships; and it still remains largely without explanation by this study, too.…”
Section: Discussionsupporting
confidence: 90%
“…In 2000, smoking in restaurants and bars was partially restricted and from june 2007 onwards, smoking has been prohibited in all bars and restaurants. Following the national smokefree legislation, population exposure to ETS has declined and smoking rates have reduced [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our results there can be left some residual confounding of smoking because we used cross-sectional survey data and smoking habits were asked only once. In addition, we could not take into account that exposure to environmental tobacco smoke (ETS) has decreased markedly in Finland from the 1980s' because of legislative smoking restrictions [25], reinforced later with smoke-free workplace legislation [26]. The ETS exposure at work has been more common in smokers than in nonsmokers, but it has decreased among smokers too and slightly also at home [25].…”
Section: Discussionmentioning
confidence: 98%
“…With the reduction in smoking prevalence and policies to restrict smoking in public places ETS exposure has been decreasing both in Europe and in the United States [17,25]. In Finland, the first law to restrict smoking was put into operation in 1977 [26], and since the 1980s' ETS exposure has decreased significantly [5]. The influence of enforcements of the tobacco laws restricting smoking at worksites in 1995 and banning of smoking in bars and restaurants in 2007 [27] can be seen also in this study as clear decreases in exposure to ETS between 1992 and 1995 and between 2007 and 2012.…”
Section: Discussionmentioning
confidence: 99%